2012
DOI: 10.7727/wimj.2011.121
|View full text |Cite
|
Sign up to set email alerts
|

The Epidemiology of Suicide in Jamaica 2002–2010: Rates and Patterns

Abstract: Objective: Suicide is increasingly recognized as a worldwide problem. There is a paucity of quality data pertaining to suicide in developing countries. Epidemiological analysis of suicide data elucidates prevailing patterns that facilitate risk factor identification and the development of germane programmatic responses. This paper analyses temporal variations in suicide rates for the years 2002-2010 in Jamaica and describes the sociodemographic profile of cases and method of suicide for the latter four years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Across depression prevalence, depression score, suicidal ideation and parasuicide, females outnumbered males with only minor exceptions: one study from Haiti found a slightly higher prevalence (92% vs 86.5%) and depression scores (x = 23.4 vs x = 21.1) among males [45]; and three studies showed slightly more parasuicide in males in Martinique and Puerto Rico [46, 47, 48]. Suicide, however, unanimously occurred more frequently by males across several countries [4956]. …”
Section: Resultsmentioning
confidence: 99%
“…Across depression prevalence, depression score, suicidal ideation and parasuicide, females outnumbered males with only minor exceptions: one study from Haiti found a slightly higher prevalence (92% vs 86.5%) and depression scores (x = 23.4 vs x = 21.1) among males [45]; and three studies showed slightly more parasuicide in males in Martinique and Puerto Rico [46, 47, 48]. Suicide, however, unanimously occurred more frequently by males across several countries [4956]. …”
Section: Resultsmentioning
confidence: 99%
“…None of the studies done on suicide on the Jamaicans population or sub-populations, have included homicide, nutritional intake, and macroeconomic variables inspite of the literature on the various bivariate associations Abel, et al, 2009Abel, et al, , 2012Abel & Martin, 2008;Burke, 1985;Irons-Morgan, 1999) or the wider Caribbean populace (Mahy, 1993). Historically, the Caribbean literature on violent crimes including homicide, has placed the emphasis from a criminology perspective (Simmonds, 2004;Robotham, 2003;Harriott, 2003Harriott, ,2004Harriott, , 2008Harriott & Brathwaite, & Wortley, 2004;Headley, 1994;Sives, 1996).…”
Section: Nutritional Intake Deficiency Suicidology and Homicide Ratementioning
confidence: 99%
“…The literature is splintered on divorce, homicide, suicide, and under-nutrition (Walker, 2005;Barker, 1998;Weitzman, 1985;Ayoub, Deutsch & Maraganorr, 1999;Amato & Keith, 1991;Zill, Morrison & Coiro, 1993;Abel et al, 2009;Abel et al, 2012;Abel & Martin, 2008;Chowdhury, 2012;Black et al, 2013), with no research bringing all the areas together. Currently, undernutrition and suicides are not major issues in Jamaica (Walker, 2005;Barker, 1998;Abel et al, 2009;Abel & Martin, 2008); but homicide, on the other hand, as well as divorce are in a pandemic phase in Jamaica, yet no information exist that explore whether those issues and others are influencing nutritional intake deficiency.…”
Section: Introductionmentioning
confidence: 99%